The role of media in attracting tourist interest in Pampang village - Rayhaniah, Sri Ayu; Dermawan, Dhyki; Wulan, Mayang; Mardiah, Ade; Karim, Qorinul (Indonesian Tourism Journal, 2024)
This study explores the role of media in promoting tourism, particularly in Pampang Village, a rural area in East Kalimantan known for its rich Dayak culture. The village is a prominent cultural tourism destination, where media, especially social media, plays a vital role in attracting tourists by highlighting its cultural and natural beauty. A qualitative descriptive method was employed to understand how media influences tourists' interests. Data was collected through in-depth interviews with tourists, direct observation of media content used for promotion, and content analysis of various media platforms. The Diffusion of Innovation theory served as the theoretical framework to analyze the spread of information about Pampang Village through social media. The study found that social media significantly enhances the visibility and appeal of Pampang Village by showcasing its unique cultural heritage. Tourists are attracted to the village through engaging content, including photos, videos, and stories that emphasize the Dayak community's traditions. Social media also facilitates direct communication between potential tourists and the village, fostering a stronger connection and personalized experience. However, challenges such as content sustainability and competition with other tourist destinations were identified. Media, particularly digital platforms, plays a crucial role in promoting Pampang Village as a cultural tourism destination. It helps build a positive image, facilitates interaction between tourists and the village, and increases tourist engagement. The findings suggest that with effective use of media, Pampang Village can enhance its tourism appeal and contribute to the local economy.